1987
DOI: 10.1002/ardp.198700018
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrylalkanoic Acids I: Syntheses and Biological Activities of 1‐Phenanthryl Derivatives

Abstract: Reformatsky reactions between 3.4‐dihydro‐1(2H)‐phenanthrenone (5) and ethyl α‐bromoacetate or propanoate yield several unsaturated esters which, upon aromatization followed by saponification, lead to the 1‐phenanthrylacetic (1) and 2‐(1‐phenanthryl)propanoic (2) acids, whose analgesic and anti‐inflammatory properties were measured and found comparable to those of Fenbufen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The Reformatsky reaction of phenanthrenones 6b , c with ethyl α-bromopropionate, followed by the dehydratation of the resulting β-hydroxyester in refluxing formic acid (Scheme ), proved to be the most convenient route leading to ethyl 2-(3,4-dihydrophenanthren-1-yl)propionates 10a − c . DDQ-promoted aromatization of the latter in benzene at 55 °C, followed by the hydrolysis of the resulting 2-phenanthrylpropionates 11a − c in methanolic KOH, afforded the corresponding 2-(phenanthren-1-yl)propionic acids 1a − c in approximately 70% overall yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Reformatsky reaction of phenanthrenones 6b , c with ethyl α-bromopropionate, followed by the dehydratation of the resulting β-hydroxyester in refluxing formic acid (Scheme ), proved to be the most convenient route leading to ethyl 2-(3,4-dihydrophenanthren-1-yl)propionates 10a − c . DDQ-promoted aromatization of the latter in benzene at 55 °C, followed by the hydrolysis of the resulting 2-phenanthrylpropionates 11a − c in methanolic KOH, afforded the corresponding 2-(phenanthren-1-yl)propionic acids 1a − c in approximately 70% overall yields.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the intrinsic importance of the selective functionalization of polycyclic arenes, our interest in this class of aromatics arose from the observation that phenanthrene nucleus is at the base of several enzyme inhibitors and other pharmacologically important drugs . In this connection, it was reported that 2-(phenanthr-1-yl)propionic acid ( 1a ) exhibits a biological activity as NSAID comparable to that of common registered profens such as fenbufen . In this article, we suggest a general approach to nucleus and/or side-chain regioselectively fluorinated 2-(phenanthryl)propionic acids on the basis of an original combination of radical and organometallic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Since the biological activity of 2-(phenanthren-1-yl)propionic acid as a NSAID was reported to be similar to that of fenbufen [8], a number of nucleus and/or side-chain fluorinated 2-phenantrylpropionic acids were prepared [9], in order to assess the effect of fluorine on the structure/activity relationship with respect to its position and to the configuration of the chiral carbon. Nevertheless, a reliable study on the relationship between stereochemistry and biological activity requires a full stereochemical characterization of the compounds under investigation.…”
Section: Introductionmentioning
confidence: 99%